Ultrasound-guided serratus plane block as an effective adjunct to systemic analgesia in four dogs undergoing thoracotomy - Asorey, Iago (Open Vet J, 2020)
BACKGROUND: Ultrasound-guided serratus plane block (UGSPB) is a loco-regional anesthesia technique designed to desensitize the thoracic wall. It is a compartmental block, where local anesthetic is delivered to the fascial, inter-muscular plane. Since its original description in humans, two cadaveric veterinary studies, redefining the technique, have been performed. Taking into account the successful use of the UGSPB in human medicine, we employed the veterinary description to perform this block in four dogs undergoing thoracotomy. The case series described below aims to share our experience of the clinical application of this new loco-regional anesthesia technique in dogs. CASE DESCRIPTION: Four dogs, with different underlying medical conditions underwent cranial lateral thoracotomy. The analgesia protocol consisted of intravenous methadone and UGSPB performed half an hour before the beginning of the procedure. The cardiovascular system was closely monitored for any signs of nociception. Fentanyl, although available as rescue analgesia, was not required in any of these cases as no signs of nociception were present. CONCLUSION: To the authors’ knowledge, this is the first veterinary clinical report using the UGSPB as a part of a multimodal analgesia protocol in dogs undergoing thoracotomy. Based on this observation, UGSPB has the potential to prevent nociception and reduce the intraoperative opioid requirements in dogs undergoing thoracotomy. A prospective randomized clinical trial is required to confirm these promising results.